Program vaksinasi dan pembentukan kader vaksinator dalam rangka pencegahan penyakit avian influenza dan newcastle disease di Desa Mandah Kecamatan Natar Kabupaten Lampung Selatan (Vaccination program and the establishment of vaccinator candidates in the context of avian influenza and newcastle disease prevention in Mandah Village, Natar Sub-District, Lampung Selatan District) - Hartono, Madi; Sirat, Muhammad Mirandy Pratama; Santosa, Purnama Edy; Siswanto, Siswanto; Ermawati, Ratna; Yudhistira, Guntur Januar; Juandita, Karina Natasya; Fatmawati, Siti Tika; Sagala, Yollanda Natalia (Universitas Syiah Kuala, 2021)
This service aims to provide knowledge to poultry farmers about the management and maintenance of poultry health, the formation of a vaccinator cadre, and the implementation of a vaccination program in Mandah Village, Natar District, South Lampung Regency. Implementing methods: 1) dissemination of information and knowledge regarding the management of poultry health and care related to the importance of vaccination, 2) Establishment of vaccinator cadres to facilitate access for the public in the implementation of vaccination based on knowledge correct, routine, and scheduled, and 3) Vaccination of poultry raised by the community for the prevention of avian influenza (AI) and Newcastle disease (ND). The target of this service is livestock groups and the community who own poultry in Mandah Village, Natar District, South Lampung Regency. Activity evaluation is carried out to determine to participants respond to the implementation of service activities by comparing changes in values in the initial evaluation (pre-test) and the final evaluation (post-test). The result of community service activities is that this activity provides tremendous benefits to the percentage of breeders' knowledge and ability before the activity of 41.65% and after the activity was carried out to 91.53%, which is in the high category. Health checks by the service team and the application of ND and AI vaccinations by the vaccinator cadres were carried out on 420 birds which are raised by breeders in Mandah Village, Natar District, South Lampung Regency. In conclusion, this activity can provide an increase in the knowledge and ability of farmers on maintenance management, health, and the importance of vaccination programs in poultry through health checks and the application of AI and ND vaccinations.